Connexin43 intercellular communication drives the early differentiation of human bone marrow stromal cells into osteoblasts. Issue 2 (23rd May 2017) - Talbot, Julie; Brion, Régis; Lamora, Audrey; Mullard, Mathilde; Morice, Sarah; Heymann, Dominique; Verrecchia, Franck
Abstract : Although it has been demonstrated that human bone marrow stromal cells (hBMSCs) express the ubiquitous connexin43 (Cx43) and form functional gap junctions, their role in the early differentiation of hBMSCs into osteoblasts remains poorly documented. Using in vitro assays, we show that Cx43 expression and gap junctional intercellular communication (GJIC) are increased during the differentiation of hBMSCs into osteoblasts, both at the protein and mRNA levels. Two independent procedures to reduce GJIC, a pharmacological approach with GJIC inhibitors (18α‐glycyrrhetinic acid and Gap27 peptide) and a molecular approach using small interfering RNA against Cx43, demonstrated that the presence of Cx43 and functional junctional channels are essential to the ability of hBMSCs to differentiate into osteoblasts in vitro. In addition, a reduced GJIC decreases the expression of Runx2, the major transcription factor implicated in the control of osteoblast commitment and early differentiation of hBMSCs into osteoblasts, suggesting that GJIC mediated by Cx43 is implicated in this process. Together our results demonstrate that GJIC mediated by the Cx43 channels plays a central role throughout the differentiation of hBMSC into osteoblasts, from the early stages to the process of mineralization. Abstract : Our results demonstrate that GJIC mediated by the Cx43 channels plays a central role throughout the differentiation of hBMSC into osteoblasts, from the early stages to the process of mineralization.